Lietuvių spaudos veikėjas Petras Vileišis. Pro memoria - Stonienė, Vanda (Knygotyra, 1993)
P. Vileišis’ (1851–1926) contribution to Lithuanian culture is rather conspicuous. Born in Lithuania, he spent many years in Russia working there as a railway engineer. In addition to large engineering activities, he was always keenly interested in Lithuanian cultural life. When studying at St. Petersburg university he took an active part in the struggle against the ban of Lithuanian press by czarist regime. With his friends he published an illegal manuscript newspaper „Kalvis melagis“. Later he was deeply engaged in writing, editing and publishing Lithuanian books. Under severe political conditions of czarist Russia it was a difficult and dangerous undertaking. In spite of all difficulties P. Vileišis managed to publish about 100 books and booklets. Many of them are translations or adaptations, but about 25 publications are written by P. Vileišis himself. The majority of them belong to popular science literature. Many of his publications appeared illegally printed in East Prussia. In 1890–1911 P. Vileišis lived in Vilnius. Engaged in large industrial manufacturing, he did not give up his previous cultural activities and took an active part in developing Lithuanian press. In 1904, the Lithuanian press ban being lifted, he established the first Lithuanian daily „Vilniaus žinios“ („News of Vilnius“). The first issues of it appeared in December, 1904, and continued its circulation up to March, 1909. In November, 1904, a printing-house was founded by him and its production included mostly Lithuanian books and newspapers. In general, P. Vileišis’ printing-house produced about 160 publications, many of them being written by Lithuanian authors. In order to spread Lithuanian publications, P. Vileišis established the book-shop „Vilniaus žinios“. Four editions of special annual catalogues informed from time to time about the printed production available in his book-shop. In 1911 P. Vileišis went to Russia. The book-shop and printing-house were sold and thus his activities in the field of Lithuanian press almost came to an end. In 1921 P. Vileišis returned to Lithuania. Here he became interested in the problems of international law, wrote some studies on Lithuanian-Polish relations (published in Paris), translated from Russian into Lithuanian a book on similar problems. P. Vileišis’ cultural activities were ignored for many decades in Lithuanian historical studies. Therefore they are not studied enough and P. Vileišis’ endeavour in the field of press is not fully evaluated and recognized. More attention should be paid to his general contribution to Lithuanian cultural development.